Alzheimer’s Diseases: Towards Biomarkers for an Early Diagnosis - Elmoualij, Benaïssa; Dupiereux, Ingrid; Seguin, Jérémie; Quadrio, Isabelle; Zorzi, Willy; Perret-Liaudet, Armand; Heinen, Ernst (IntechOpen, 2011)
None